Pengaruh Relaksasi Otot terhadap Performansi Memori Jangka Pendek Penderita Diabetes Mellitus - Fenty Puspitasari; Diana Setiyawati (Universitas Islam Indonesia, 2009)
Several studies showed that most of diabetes mellitus patients experience a cognition function decrease, including short-term memory performance. The research is aimed for identifying the effect of muscular relaxation on a short-term memory performance among diabetes mellitus patients. Control Group Pre-test-Posttest Design was used, with twenty eight participants were divided equally into experiment and control groups. Filling stem completion test was used to asses the short term memory performance. The result showed that muscular relaxation didn't cause significant increase in short term memory performance, due to the fact that individual achievements were varied in conducting the muscular relaxation, the nature of the muscular relaxation is subjective and other aspects in this research were failed to control.Keywords: Muscular relaxation, short-term memory performance, diabetes mellitus.